Effect of postural sway scale as a prognostic tool in low back pain management. - MANJULADEVI.N B.P.T,; Dr.R.ARUNACHALAM MPT(Neuro), Ph.D,,; B.PRUDHVI TEJASRI B.P.T, M.P.T,; Dr.KUMARESAN MPT(Neuro),; Dr.KIRUTHIKA MPT(Neuro), (International Journal of Pharma and Bio Sciences, 2017)
A study to the postural sway in normal and subjects with low back pain, the influence of physiotherapy on postural sway and the effectiveness of postural scale as a prognostic tool. The study was done in three different phases as follows : PHASE – 1- Sway measurement was done for the normal subjects and for the subject with low back pain on a stable ground using lord sway meter and a comparison was drawn between them. PHASE- 2- subjects with low back ache were provided with physiotherapy management, sway was measured before and after treatment. PHASE- 3 - The sway variations were also compared with Oswestry disability rating scales to assess the correlation between the prognostic values of the tools. There is significant difference in lateral sway and antero posterior sway between subject with low back pain and age related normal. (P =0.0001). Analysis of sway measures before and after physiotherapy intervention showed a significant difference ( P=0.0001). There was a high correlation between the sway values and the Oswestry disability rating scales. This study concluded that there is an altered sway pattern in subjects with low back pain, this pattern of sway can be normalised by physiotherapy intervention. This study also concludes that the postural sway meter can be used as one of the outcome measure in the low back pain rehabilitation.